Comparison of Attention for Neurological Research on Social Media vs Academia: An Altmetric Score Analysis - Punia, Vineet (JAMA Neurol, 2019)
This study compared Altmetric scores of neurological research as a marker of “buzz” with citations as a marker of academic attention.